2018
DOI: 10.26464/epp2018014
|View full text |Cite
|
Sign up to set email alerts
|

The 13 November 2016 Kaikoura, New Zealand Earthquake: rupture process and seismotectonic implications

Abstract: The 13 November 2016 Kaikoura earthquake occurred in the northeastern coastal region of the South Island, New Zealand. The Mw 7.8 mainshock generated a complex pattern of surface ruptures, and was followed within about 12 hours by three moderate shocks of Mw ≥ 6.0. Here we use teleseismic waveforms to invert for the source rupture of the Kaikoura earthquake. The resulting slip‐distribution model exhibits insignificant slip near the hypocenter and three pockets of major slip zones with distinct senses of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In fact, at least 12 mapped and unmapped faults with varieties of focal mechanisms were involved in this event (Hamling et al, ; Kaiser et al, ), and most of them were of strike‐slip types. Duputel and Rivera () employed three strike‐slip events and one thrust‐slip event in order to explain the main feature of ground motion, and thought the first event around the epicenter should be of the strike‐slip type and the thrust‐slip event should be at the northern end; but we feel strongly that the purely thrust event should be under all the strike‐slip events, that more strike‐slip events should be on northern area (around asperity B) than on the southern area (around asperity A), and that a possible model should be like the one shown in Figure , which is similar to the model proposed by Lo et al (). Of course, more comprehensive investigation and study will be required in order to clarify this.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, at least 12 mapped and unmapped faults with varieties of focal mechanisms were involved in this event (Hamling et al, ; Kaiser et al, ), and most of them were of strike‐slip types. Duputel and Rivera () employed three strike‐slip events and one thrust‐slip event in order to explain the main feature of ground motion, and thought the first event around the epicenter should be of the strike‐slip type and the thrust‐slip event should be at the northern end; but we feel strongly that the purely thrust event should be under all the strike‐slip events, that more strike‐slip events should be on northern area (around asperity B) than on the southern area (around asperity A), and that a possible model should be like the one shown in Figure , which is similar to the model proposed by Lo et al (). Of course, more comprehensive investigation and study will be required in order to clarify this.…”
Section: Discussionmentioning
confidence: 90%
“…We think there are two possible causes. One is that the InSAR observation itself has been in question because of its special geographical location, and the other is that our simple plane model is incapable of explaining the InSAR observation along the coastal line, which previous studies have revealed to be largely dominated by local tectonics (Hamling et al, ; Cesca et al, ; Lo et al, ) .…”
Section: Tempo‐spatial Distribution Of the Slipmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, an earthquake of 7.5 triggered by an underwater landslide caused a tsunami on 28 September 2018 in Indonesia; 22 buoys connected to the seafloor had not been functioning for 6 years due to a lack of funding [4]. On the other hand, New Zealand has a DART sensor system of 12 sensors, which is further connected to other global partners for the real transmission of data [5]. Although using satellites is one of the commonly used technologies for tsunami detection, it can take up to five minutes to issue an early warning after tsunami detection [6].…”
Section: Introductionmentioning
confidence: 99%